The key factor of mitochondrial biogenesis is PGC-1α in physiological and pathological conditions - Marina Yu. Strekalovskaya (Clinical Medicine (Russian Journal), 2026)
This study presents an analysis of the functional activity of the peroxisome proliferator receptor (PPAR) coactivator (PGC-1α) in both physiological and pathological conditions. PGC-1α is a multifunctional regulatory factor that controls all mitochondrial life cycle processes, including biogenesis, division, fusion, and mitophagy, enhances the expression of a wide range of genes, and is involved in the development of many diseases, such as cancer, heart and cardiovascular diseases, neurological disorders, kidney diseases, motor systems, and metabolic disorders. Aim. To summarize the results of modern scientific research on the role of PGC-1α in physiological and pathological conditions. Material and methods. This descriptive literature review provides an analysis of scientifi c studies conducted in domestic and foreign databases on the functional activity of PGC-1α, which plays a crucial role in regulating the transcription of genes related to energy metabolism, mitochondrial biogenesis, and cellular adaptation to various metabolic demands, from 2001 to 2024. Discussion. Literature data analysis has shown that PGC-1α is highly versatile and can increase the transcriptional activity of many nuclear receptor families and other transcription factors. PPARs (PPAR-α, PPAR-δ, and PPAR-γ) are a family of nuclear receptors, and they are all co-activated and transcribed by PGC-1α, PPAR-γ, which is essential for adipogenesis and differentiation, while PPAR-α and PPAR-δ play important roles in controlling fatty acid oxidation.